HUBUNGAN ANTARA FLAT FOOT DENGAN KESEIMBANGAN PADA ANAK DOWN SYNDROME DI YAYASAN PENDIDIKAN LUAR BIASA NUSANTARA DEPOK - Rhaudya Salsa Amalia (2023)
Abstract Background : Down syndrome is a condition that has an extra copy of chromosome 21. As much as 20% to 27% of children with Down syndrome experience musculoskeletal disorders. Up to 66% of children with Down syndrome have foot abnormalities associated with low muscle tone (hypotonia) and children with Down syndrome also experience impaired motor development, causing balance problems. Research Purposes : To be able to determine the relationship between flat foot and balance in children with Down syndrome at Yayasan Pendidikan Luar Biasa Nusantara Depok. Methods : This study uses a correlational quantitative research design with a cross-sectional approach. With a sample of 80 children with Down syndrome with an error rate of 5%. This research was conducted offline using a footprint test and a pediatric balance scale questionnaire. Research Result : The results obtained were in the category of soles of children with Down syndrome, the highest sample was in the category of flat feet degree 2 with an intermediate risk of falling, namely with a percentage of 33.8%, while for the category with the least number, namely in the category of flat feet degrees 3 with a category of low falls with a percentage of 0.0%. After the correlation test that there is no relationship between flat foot and balance, and a correlation coefficient of 0.568 has a unidirectional value. The conclusion of this study resulted that there is no relationship between flat foot and unidirectional balance.